1998
DOI: 10.1017/s0033291798006874
|View full text |Cite
|
Sign up to set email alerts
|

Why GHQ threshold varies from one place to another

Abstract: The GHQ threshold is partly determined by the prevalence of multiple diagnoses, with higher thresholds being associated by higher rates of both single and multiple diagnosis. The mean GHQ score for the whole population of respondents provides a rough guide to the best threshold. In those centres where the discriminatory power of the GHQ is lowest, it is necessary to use a low threshold as a way of ensuring that sensitivity is protected, but the positive predictive value of the GHQ is then lower. Some of the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
319
2
9

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 386 publications
(334 citation statements)
references
References 2 publications
4
319
2
9
Order By: Relevance
“…Each participant's 12 binary scores were then summed to create a GHQ-12 score, which could range between 0 and 12, with higher values indicating poorer mental health (Cronbach's α = 0.89). Goldberg et al (1998) suggested that the optimal cut-off threshold for the GHQ-12 should be between 3 and 4 (with a score of 3 indicating the absence of a mental disorder, and a score of 4 indicating the presence of a mental disorder). Moreover, Hardy et al (1999) claimed that this threshold gives the best conservative estimate of minor psychiatric morbidity.…”
Section: Mental Healthmentioning
confidence: 99%
“…Each participant's 12 binary scores were then summed to create a GHQ-12 score, which could range between 0 and 12, with higher values indicating poorer mental health (Cronbach's α = 0.89). Goldberg et al (1998) suggested that the optimal cut-off threshold for the GHQ-12 should be between 3 and 4 (with a score of 3 indicating the absence of a mental disorder, and a score of 4 indicating the presence of a mental disorder). Moreover, Hardy et al (1999) claimed that this threshold gives the best conservative estimate of minor psychiatric morbidity.…”
Section: Mental Healthmentioning
confidence: 99%
“…In regard to choice of caseness threshold or cut-off score, previous Gulf War studies (Unwin et al 1999) using the GHQ-12 have solely involved UK veterans and employed a fixed cut-off of three or more symptoms. There is strong evidence, however, that optimal GHQ cut-off scores vary geographically (Goldberg et al 1997(Goldberg et al , 1998. Donath (2001) found the optimal cut-off for the general Australian population to be one or more symptoms.…”
Section: Instrumentsmentioning
confidence: 99%
“…In our study, the reference standard was an assessment made by a psychiatrist using consistent standard criteria. The various methods give different results because of diversity in defining 'caseness' 10 . Goldberg 4 reported that the 'Clinical Interview Schedule' is almost identical to that which is used for the 'Present State Examination' in determining the validity.…”
Section: Discussionmentioning
confidence: 99%